Management of Patellar Instability: A Network Meta-analysis of Randomized Control Trials. Issue 9 (July 2022) - Hurley, Eoghan T.; Colasanti, Christopher A.; Anil, Utkarsh; McAllister, Delon; Matache, Bogdan A.; Alaia, Michael J.; Strauss, Eric J.; Campbell, Kirk A.
Background: Multiple surgical options exist for the treatment of patellar instability; however, the most common procedures involve either a reconstruction of the medial patellofemoral ligament (MPFL) or a repair/plication of the MPFL and medial soft tissues. Purpose: To perform a network meta-analysis of the randomized controlled trials (RCTs) in the literature to compare MPFL reconstruction, MPFL repair, and nonoperative management for patellar instability. Study Design: Systematic review and network meta-analysis; Level of evidence, 1. Methods: The literature search was performed based on the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. RCTs comparing MPFL reconstruction, MPFL repair, and nonoperative management for patellar instability were included. Clinical outcomes included recurrent instability (including both dislocations and subluxations), redislocation, and Kujala score. Clinical outcomes were compared using a frequentist approach to network meta-analysis, with statistical analysis performed using the statistical software R. The treatment options were ranked using P scores. Results: There were 13 RCTs with a total of 789 patients, all with a minimum follow-up of 24 months. There were 150 patients treated using MPFL reconstruction, 353 treated using MPFL repair, and 286 treated nonoperatively. Overall, MPFL reconstruction had the highest P score (0.9967) and resulted in a significantly lower recurrence rate than did MPFL repair (odds ratio [OR], 0.42; 95% CI, 0.07-0.72) and nonoperative management (OR, 0.09; 95% CI, 0.03-0.32). In addition, MPFL repair resulted in a significantly lower recurrence rate than did nonoperative management (OR, 0.42; 95% CI, 0.25-0.70). MPFL reconstruction had the highest P score (0.9651) and resulted in a significantly higher Kujala score than did nonoperative management (mean difference, 10.45; 95% CI, 0.41-20.49) but not MPFL repair (mean difference, 0.15; 95% CI, 0.03-0.68). Subgroup analysis revealed that MPFL reconstruction had the highest P score for all outcomes in those with first-time dislocation. Conclusion: The current study demonstrated that MPFL reconstruction results in the lowest rate of recurrent patellar instability and best functional outcomes as measured using the Kujala score.